An Investigation into the Effect of Cracking on the Response of Drilled and Postgrouted Concrete Pipe Pile under Lateral Loading - Zhijun Yang; Qing Fang; Bu Lv; Can Mei; Xudong Fu (Advances in Materials Science and Engineering)
The cracks are likely to initiate on a lateral loaded pile and would cause greater deflection at the pile head. However, there is a lack of thorough investigation into the effect of cracking on the response of the lateral loaded pile. In this article, a full-scale field test was carried out to investigate the behavior of Drilled and Postgrouted Concrete Pipe Pile under lateral loads. A novel analysis method for the lateral loaded pile, which can take the cracking effects into consideration, was proposed, and the validity was verified by the test results. With the proposed method, the cracking effects on flexural rigidity, displacement, rotation, and bending moment of the pile were studied. In brief, cracking effect would dramatically reduce the flexural rigidity of the pile, remarkable increase the displacement and rotation of the pile top, and slightly decrease bending moment of the pile. Unambiguously, the results show that the proposed method can excellently predict the response of laterally loaded piles under cracking effects.